Strategic Management and Shared Vision in Micro and Small Enterprises - Lima, Edmilson (2013)
This essay addresses aspects of strategic management in micro and small enterprises (MSEs) that are not usually treated in the literature, especially regarding the development and sharing processes of directors’ vision based on strategic conversation. It follows a systemic learning approach, which is descriptive and based on soft systems methodology, an interpretive perspective of systems theory. Its central concepts are vision and learning. First, however, the essay justifies the need for this type of approach, describes the potential contribution of the vision and learning concepts, and characterizes the approach itself by exploring the literature. The resources employed to develop this article are primarily the available literature, various examples, argumentation, and description. The contributions that it generates include a differentiated perspective to understand strategic management of MSEs, more knowledge about certain aspects scarcely addressed in previous studies, and potentially useful themes and understandings for further studies.